On the use of time division multiplexing to improve electrical brain stimulation focality. (August 2020) - Abouelseoud, Gehan; Abouelseoud, Yasmine; Shoukry, Amin; Ismail, Nour; Mekky, Jaidaa
Highlights: Selective (focal) stimulation of target brain locations is difficult. Time division multiplexing (TDM) improves the focality of complex stimulation tasks. An appropriate time gap needs to be inserted between the time division slots. Using TDM improves the accuracy of cortical vision prostheses. The used mathematical model facilitates prostheses optimization and design tuning. Abstract: Background and objective: Selective electrical stimulation of target brain locations (stimulation focality) is a difficult problem because it comprises conflicting goals. The stimulating current density field needs to be strong enough to stimulate targeted locations but weak enough not to stimulate near-by non-targeted locations. The objective of this study is to suggest a methodology for improving electrical stimulation focality based on time-division multiplexing principle. Proposed methodology: The complex problem of exciting a group of target locations is decomposed into a series of simpler problems in which a single location is targeted. Time-division multiplexing between the solutions of the simpler problems achieves seemingly parallel excitation of the selected target locations with minimal excitation of non-targeted locations. Results: A high fidelity finite element-based simulation of a cortical vision prosthesis is used to demonstrate the proposed idea and highlight important facts about neurons dynamics that must be taken into consideration in order to design a successful time-division multiplexing based stimulation scheme. Conclusion: The study offers a clear detailed procedure for designing focal electrical stimulation setups based on time division multiplexing principle. The included results and experiments prove that the proposed strategy is a step forward towards more focal stimulation setups.